The impact of e-mobility on petrol stations in the Czech Republic - Kašpar, Jan (2021)
E-mobility is a frequently discussed topic in today’s world, primarily in the context of efforts to mitigate global warming and reduce carbon emission and pollution levels. The increasing e-mobility will impact numerous industries. The fuel retail industry will be affected significantly. Petrol stations businesses will face unprecedented pressures resulting from the rising number of electric vehicles worldwide. This thesis focuses on electric mobility in relation to the fuel retail industry in the Czech Republic. It outlines the future impact of increasing e-mobility and electric vehicles on petrol stations in 2040. The thesis uses scenario planning methodology to illustrate such impact. Overall, four different future scenarios have been developed. These scenarios demonstrate different futures and vary in the level of impact e-mobility will have on petrol stations in the Czech Republic.